KAIDAH PENGELOLAAN BARANG MILIK NEGARA BERUPA RUMAH NEGARA MENURUT PERATURAN PERUNDANGAN MENUJU PENGELOLAAN YANG TERTIB DAN AKUNTABEL - Taswin Taswin; Arywarti Marganingsih (Jurnal Ekonomi dan Bisnis, 2025)
The management of State-Owned Property in the form of State Houses towards orderly and accountable management requires eflorts to organize its management. There are several problems encountered related to the management of State-Owned Property in the form of State Houses. The government has issued laws and regulations concerning the Management of State Property in the form of State Houses which aim to realize the management of State-Owned Property in the form of State Houses that is orderly and accountable. The research method used is a normative legal approach to explore provisions and through literature research/reviews. The rules that must be used in the management of State-Owned Property in the form of State Houses include the steps for managing State-Owned Property in the form of State Houses starting from planning, procurement, occupancy, maintenance, administration, division of authority and responsibility, organizational structure of management, security, and supervision and control. Handling of state assets in the form of State-Owned Property in the form of State Houses that follows the rules of good governance is one of the important basic capitals in preparing accountable reports.